1992
DOI: 10.1190/1.1443313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heterogeneities and anisotropy on sonic and ultrasonic attenuation in rocks

Abstract: We compare the attenuation obtained by the resonant bar technique in the sonic frequency range (3–10 kHz) with that obtained by the pulse transmission technique in the ultrasonic frequency range (500 kHz) on a set of 30 rocks, including sandstones and limestones. The sonic and ultrasonic measurements were performed under high effective pressure on adjacent water‐saturated samples from each rock block. Compressional ultrasonic attenuation was typically larger than extensional sonic attenuation, particularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 14 publications
5
29
0
1
Order By: Relevance
“…A schematic illustration of the experimental setup is shown in Figure 2. A pulse transmission method (Toksöz et al, 1979;Lucet and Zinszner, 1992) was used to measure the decay of amplitude of the propagating wave in the sample. This technique measures attenuation relative to a reference sample, which has very low attenuation.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
“…A schematic illustration of the experimental setup is shown in Figure 2. A pulse transmission method (Toksöz et al, 1979;Lucet and Zinszner, 1992) was used to measure the decay of amplitude of the propagating wave in the sample. This technique measures attenuation relative to a reference sample, which has very low attenuation.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
“…Kiister and Toksoz (1974a), Kiister and Toksoz (1974b), Plona and Johnston (1981), , Winkler and Murphy (1984), Blair (1990), Lucet and Zinszner (1992) Squirt Fluid Flow Mavko and Nur (I979), Palmer and Traviolia (1981), Bulau et. al, (1984), Dvorkin et.…”
Section: Proposed Attenuation Mechanisms In Granular Media and Associmentioning
confidence: 99%
“…Also, both the seismic field observations and lab studies have demonstrated that most sedimentary rocks display long-wavelength anisotropy, so the anisotropy relates closely with visco-elasticity (Lucet and Zinszner, 1992). Visco-elastic anisotropic media has been researched for many years.…”
Section: Introductionmentioning
confidence: 98%